Can changes in soil properties in organic banana production suppress fusarium wilt? - Geense, P; Pattison, A.B.; Kukulies, T.L.; Scholberg, J.M.S.; Molina, A.B. (Scientific Research Publishing, Inc., 2015)
Organic agriculture promotes disease suppression through healthy soils by increasing biological activity and diversity through the application of organic fertilizers and increasing organic inputs. Fusarium wilt of bananas (Fusarium oxysporum f. sp. cubense) (Foc), also known as Panama disease, has been a devastating disease throughout the world. So far, no fungicides or cultural measures have been found that control Foc sufficiently. The aim of this research was to assess whether organic-based farming systems were more resilient than inorganic farming systems to soil borne diseases, in particular Fusarium wilts. A survey was conducted comparing five organic and five conventional banana plantations at paired sites in north Queensland, Australia. Soil samples were collected and analysed for chemical, physical and biological soil health indicators. Disease development of F. oxysporum f. sp. lycopersici in tomatoes and Foc in bananas were studied in pot trials to pursue clues for identifying Fusarium suppressive soil traits. Organic soils from the survey showed higher microbial activity and lower disease symptom expression (both with tomatoes and bananas) than conventional soils. In the survey, nematode diversity and soil sulphate content were recurring indicators in all experiments showing close correlations to pathogen growth, disease expression and plant health. Organic soils were lower in plant-parasitic nematodes and sulphate sulphur levels and higher in nematode diversity, labile soil C and microbial indicators. Soil conduciveness or suppression of Foc appeared to be largely governed by competition for carbon. Measurement of soil microbial enzyme activity, nematode community structure and diversity and possibly sulphate sulphur seem to provide a relatively reliable indicator for general disease suppression. Differences between organic and conventional agriculture cannot be related to single management practices, but may be linked to synergies among system components.